Role of Circulating T Follicular Helper Cells and Stem-Like Memory CD4+ T Cells in the Pathogenesis of HIV-2 Infection and Disease Progression - Ponnan, Sivasankaran Munusamy; Vidyavijayan, K.K.; Thiruvengadam, Kannan; Hilda J, Nancy; Mathayan, Manikannan; Murugavel, Kailapuri Gangatharan; Hanna, Luke Elizabeth (Frontiers in Immunology, 2021)
CD4+ T cells are critical players in the host adaptive immune response. Emerging evidence suggests that certain CD4+ T cell subsets contribute significantly to the production of neutralizing antibodies and help in the control of virus replication. Circulating T follicular helper cells (Tfh) constitute a key T cell subset that trigger the adaptive immune response and stimulate the production of neutralizing antibodies (NAbs). T cells having stem cell-like property, called stem-like memory T cells (Tscm), constitute another important subset of T cells that play a critical role in slowing the rate of disease progression through the differentiation and expansion of different types of memory cell subsets. However, the role of these immune cell subsets in T cell homeostasis, CD4+ T cell proliferation, and progression of disease, particularly in HIV-2 infection, has not yet been elucidated. The present study involved a detailed evaluation of the different CD4+ T cell subsets in HIV-2 infected persons with a view to understanding the role of these immune cell subsets in the better control of virus replication and delayed disease progression that is characteristic of HIV-2 infection. We observed elevated levels of CD4+ Tfh and CD4+ Tscm cells along with memory and effector T cell abundance in HIV-2 infected individuals. We also found increased frequencies of CXCR5+ CD8+ T cells and CD8+ Tscm cells, as well as memory B cells that are responsible for NAb development in HIV-2 infected persons. Interestingly, we found that the frequency of memory CD4+ T cells as well as memory B cells correlated significantly with neutralizing antibody titers in HIV-2 infected persons. These observations point to a more robust CD4+ T cell response that supports B cell differentiation, antibody production, and CD8+ T cell development in HIV-2 infected persons and contributes to better control of the virus and slower rate of disease progression in these individuals.